PERAN ORANG TUA DALAM PENGGUNAAN METODE SELF BUILDING AT HOME ANAK TUNAGRAHITA PADA PEMBELAJARAN ADL (ACTIVITY DAILY LIVING) - Eryo Kukuh Prastyo; Haryu Islamudin (UIN Kiai Haji Achmad Siddiq Jember, 2021)
This study aims to describe and explain the role of parents in assisting the learning of mentally retarded children and to describe the effectiveness of the Self-building At Home method of SDLB YPAC Jember students in ADL (Activity Daily Living) assistance as well as to find out what obstacles and obstacles people experience. parents in accompanying children while studying at home. The focus of the problems studied in this thesis are: 1) How is the role of parents in mentoring children with intellectual disabilities with the method of Self building At Home for SDLB YPAC Jember students?, 2) How is the effectiveness of the Self-building At Home method for SDLB YPAC Jember students in ADL (Activity) assistance Daily Living)? 3) What are the obstacles and obstacles experienced by parents in assisting the learning of mentally retarded children at home? This study uses a qualitative method with a descriptive approach, analyzing the process of implementing the Self-building At Home method in learning the daily living activities of SDLB YPAC Jember students. The data collection techniques used semi-structured interviews, participatory observation and documentation. For data analysis using data reduction, data presentation and verification, while for data validity using source triangulation and technical triangulation. This study concluded 1) the role of parents is very important for the development of student learning at home during the pandemic. 2) learning activity daily living is quite effective carried out at students' homes with a visiting teacher model. The learning is carried out one week 2-3 times during the pandemic, depending on the situation and condition of the students. 3) the obstacles experienced by parents when accompanying mentally retarded children's learning during the pandemic, namely the boredom of children in learning, in overcoming these obstacles parents do what their children like first so that children can get excited again in learning.